Identification and Characterization of pvuA, a Gene Encoding the Ferric Vibrioferrin Receptor Protein in Vibrio parahaemolyticus - Funahashi, Tatsuya (American Society for Microbiology, 2002)
We previously reported that Vibrio parahaemolyticus expresses two outer membrane proteins of 78 and 83 kDa concomitant with production of siderophore vibrioferrin in response to iron starvation stress and that these proteins are the ferric vibrioferrin receptor and heme receptor, respectively (S. Yamamoto, T. Akiyama, N. Okujo, S. Matsuura, and S. Shinoda, Microbiol. Immunol. 39:759-766, 1995; S. Yamamoto, Y. Hara, K. Tomochika, and S. Shinoda, FEMS Microbiol. Lett. 128:195-200, 1995). In this study, the Fur titration assay (FURTA) system was applied to isolate DNA fragments containing a potential Fur box from a genomic DNA library of V. parahaemolyticus WP1. Sequencing a 3.2-kb DNA insert in one FURTA-positive clone revealed that an amino acid sequence deduced from a partial gene, which was preceded by a full-length gene (psuA) encoding a receptor for a siderophore of unknown origin, was consistent with the N-terminal amino acid sequence of the 78-kDa ferric vibrioferrin receptor. Then, the full-length gene (pvuA) encoding the ferric vibrioferrin receptor was cloned and characterized. The deduced protein encoded by pvuA displayed the highest similarity (31% identity; 48% similarity) to RumA, a ferric rhizoferrin receptor of Morganella morganii. Primer extension and Northern blot analyses indicated that psuA and pvuA constitute an operon which is transcribed from a Fur-repressed promoter upstream of psuA. The product of the pvuA gene and its function were confirmed by generating a pvuA-disrupted mutant, coupled with genetic complementation studies. A mutant with disruption in the upstream psuA gene also displayed a phenotype impaired in the utilization of ferric vibrioferrin.